2021
DOI: 10.1126/sciadv.abg5285
|View full text |Cite
|
Sign up to set email alerts
|

Predicting future from past: The genomic basis of recurrent and rapid stickleback evolution

Abstract: Similar forms often evolve repeatedly in nature, raising long-standing questions about the underlying mechanisms. Here, we use repeated evolution in stickleback to identify a large set of genomic loci that change recurrently during colonization of freshwater habitats by marine fish. The same loci used repeatedly in extant populations also show rapid allele frequency changes when new freshwater populations are experimentally established from marine ancestors. Marked genotypic and phenotypic changes arise within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 125 publications
6
59
0
Order By: Relevance
“…To identify novel loci controlling adaptations in threespine stickleback, we measured dorsal spine 1 (DS1), dorsal spine 2 (DS2), and pelvic spine (PS) length on 115 fish previously used for whole-genome sequencing ( 18 ). These major spines vary significantly in size among stickleback populations, including different freshwater populations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To identify novel loci controlling adaptations in threespine stickleback, we measured dorsal spine 1 (DS1), dorsal spine 2 (DS2), and pelvic spine (PS) length on 115 fish previously used for whole-genome sequencing ( 18 ). These major spines vary significantly in size among stickleback populations, including different freshwater populations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have identified genomic sequences that show prominent differentiation between most marine and freshwater stickleback ( 16 18 , 50 , 51 ). Having identified multiple alleles at Maser that are associated with contrasting phenotypes among different freshwater populations, we searched stickleback genome sequences for other loci that also show triallelic differentiation among diverse populations from the Pacific Northwest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations